2015
DOI: 10.1016/j.outlook.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of deployment on military families with young children: A systematic review

Abstract: More research using multiple methods, stronger designs, and more diverse samples is needed to understand and address the needs of military families with young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 60 publications
0
33
0
Order By: Relevance
“…1,35 A systematic review of 26 studies found an association between increased deployment-related stress and mental health problems in parents and young children as well as increased use of mental health resources. 36 One of these studies demonstrated an increase in outpatient and well-child visits during deployment for children of married parents, which may be attributed to the effect of deployment-related stress on the spouse who was not deployed. 37 Conversely, the authors found decreased visits for children of single parents, which may be attributed to a decreased effect of deployment on a nonparent caregiver or lack of familiarity navigating the health care system.…”
Section: Health Care Usementioning
confidence: 99%
“…1,35 A systematic review of 26 studies found an association between increased deployment-related stress and mental health problems in parents and young children as well as increased use of mental health resources. 36 One of these studies demonstrated an increase in outpatient and well-child visits during deployment for children of married parents, which may be attributed to the effect of deployment-related stress on the spouse who was not deployed. 37 Conversely, the authors found decreased visits for children of single parents, which may be attributed to a decreased effect of deployment on a nonparent caregiver or lack of familiarity navigating the health care system.…”
Section: Health Care Usementioning
confidence: 99%
“…This finding has emerged in studies of children and adolescents in the United States , Canada , and Britain , as well as in studies of adult children of fathers deployed to earlier conflicts from other countries, including Israel and Africa . In addition, children are more likely to be depressed or have behavioral problems when deployment distresses the spouse or partner of the deployed service member, while parents are often the source of data about children, which may dilute the finding . Although many studies consider children's sex and age, no consistent patterns have emerged .…”
Section: What Factors Boost or Blunt The Effects Of Deployment On Chimentioning
confidence: 99%
“…In addition, children are more likely to be depressed or have behavioral problems when deployment distresses the spouse or partner of the deployed service member, while parents are often the source of data about children, which may dilute the finding (24,29). Although many studies consider children's sex and age, no consistent patterns have emerged (30).…”
Section: What Factors Boost or Blunt The Effects Of Deployment On Chimentioning
confidence: 99%
See 1 more Smart Citation
“…Another factor was the emerging institutional embrace of a systemic understanding of the ways in which a service member's family and children are also impacted by wartime deployments and that the health and well‐being of this primary supportive context was central to the task of maintaining force readiness and the ability of service members to perform in repeated, sometimes back to back deployments (American Psychological Association Presidential Task Force, ; Glynn, ; Institute of Medicine, ; US DOD, ). From 2001 to 2014 there was an explosion of research on the effects of wartime deployment, combat exposure, parental PTSD, traumatic brain injury, and a host of other war‐related conditions on military children, spouses, and the quality of marital and family functioning (Chandra et al., ; Creech, Hadley, & Borsari, ; U.S. Department of Defense, ; Flake, Davis, Johnson, & Middleton, ; Institute of Medicine, ; Sheppard, Weil Malatras, & Israel, ; Trautmann, Alhusen, & Gross, ). Collectively, these studies have offered empirical support for systemic models of family functioning and a more nuanced understanding of the mechanisms by which stress and trauma reverberate across family and partner relationships (Chandra et al., ; Gewirtz, McMorris, Hanson, & Davis, ; MacDermid Wadsworth, ; Paley, Lester, & Mogil, ).…”
Section: Introductionmentioning
confidence: 99%